Changing orientation of x-ray radiator to vary x-ray radiation - FREUDENBERGER JOERG; BERNHARDT, PHILIPP (2025)
The invention relates to a method for generating X-ray radiation having X-ray properties, comprising the following steps: providing first examination type information and second examination type information for selection by means of an input means; receiving the selected check type information in the control unit; -selecting an X-ray radiator configuration from a plurality of X-ray radiator configurations by means of the control unit in dependence on the received examination type information; determining a control signal in dependence on the selected X-ray radiator configuration; automatically setting a mechanical adjustment unit of the X-ray emitter in accordance with the determined control signal in order to change the orientation of the X-ray emitter with respect to the recording region; and generating X-ray radiation having X-ray properties by means of an X-ray emitter provided for transmission of the examination object in the recording region. 本发明涉及一种用于产生具有X射线特性的X射线辐射的方法，所述方法包括以下步骤：-提供第一检查类型信息和第二检查类型信息，以